ANALISIS KERAPATAN STASIUN HUJAN PADA DAS OYO - , DENO ISVHARA K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rainfall data is needed as a major input in the hydrological analysis, both for planning and management of water recources. Accurate rainfall data needed to obtain accuracy in analysis. The number of rainfall stations, density and network pattern also accuracy of data recording are should be considered in order to obtain an accurate rainfall data. This study was conducted in Daerah Istimewa Yogyakarta, with area of research on Oyo Watershed that purpose to get the optimal number of rainfall stations and its network to retrieved data that actually represents the depth of the actual rain. The required data are secondary data such as a map of the Watershed and rainfall data. The analysis for network density of rainfall stations is calculated using Kagan method, then the network of rainfall stations is drawn based on the number of stations that have been obtained. Based on analytical result, the coefficient of correlation for daily rainfall is 0,316 and for monthly rainfall is 0,785. These values are relatively small, it indicates that the rain that occurred are varied. The number of rainfall stations at Oyo Watershed for each alignment error 5% and 10 % for daily rainfall are needed 7 stations with the density 106,55 km2/station and 3 stations with the density 248,63 km2/station. Meanwhile for alignment error 5% for monthly rainfall is only needed 1 station with the density 745,88 km2/station. Keywords : Rainfall station , density, Kagan method